César Vallejo´s Essential Poetry - Martos Carrera, Marco (Espergesia, 2019)
The themes about César Vallejo’s poetry are inexhaustible, and so this article attempts to relate the author’s life experiences to his poetics, especially in Los heraldos negros (The Black Heralds). To achieve this purpose, the context in the years of formation of the poet from Santiago have been taken into account as well as his correlation with other authors and the existing movements during that time. When dealing with The black heralds, we point out how he becomes a different poet because of his sensitivity in confronting the time he had to live with universal themes, such as the originality of the nature of pain, known by all human beings. Then in Trilce, it is the different and crucial events of his life that mark him in a brutal way, and it becomes the genesis of the work. España, aparta de mi este cáliz stands out as he achieves epic accents that are no longer present in his contemporary life because the poems have a political force and identification with a particular republican side, which, read during this time, represent the idea of solidarity and the symbolic possibility of defeating death. Already in Poemas humanos, Vallejo is the poet of pain, but also of hope and solidarity. Another important subject that has also been addressed in this work is love, seen from the perspective of psychoanalysis, which becomes a receptive form of unresolved Oedipus complex. However, it is later overcome just like love conflicts are.